Rhizobium spp. strains with biofertilizer potential: Multivariate selection and their tolerance to critical conditions of tropical soils (UNED Research Journal, 2026)
Introduction: Leguminous plants establish symbiotic relationships with bacteria of the genus Rhizobium, which represent an important source of organic nitrogen in sustainable production. However, successful bacterial colonization remains a challenge due to the variability of soil conditions and current agronomic practices. Objective: To select Rhizobium spp. strains based on their tolerance to salinity and aluminum toxicity, and to evaluate their effect on the foliar mineral content of common bean (Phaseolus vulgaris). Methods: We did triplicate assays on Rhizobium spp. strains, from a Costa Rican laboratory, selected for siderophore production, phosphorus solubilization, and tolerance to salinity and aluminum toxicity. In greenhouse, we filled 4-L pots with soil that had been autoclaved twice. We inoculated seeds of the Guaymí and Cabécar varieties at sowing with the selected strains at a concentration of 10⁸ CFU. We established five treatments: T1 (CIAT899), T2 (CR4019B), T3 (CIAT899 + CR4019B), T4 (urea), and T5 (control), with four replicates in a randomized design. We terminated the experiment at flowering and analyzed foliar tissue chemistry. Results: Salinity was a major limiting factor for most strains, and aluminum exposure restricted growth. The strains CIAT899 and CR4019B had high phosphorus solubilization and lower siderophore production. Inoculation increased foliar nitrogen content in both varieties and resulted in significant differences in calcium, zinc, and boron in the Guaymí variety, with no differences in foliar nitrogen compared to the urea treatment. Conclusion: Responses depend on cultivar, emphasizing the need to select compatible strains and genotypes. Overall, Rhizobium spp. offers a sustainable alternative because inoculation with selected strains (particularly CIAT899 and CR4019B), enhances phosphorus solubilization and siderophore production, improving the availability and uptake of essential nutrients in P. vulgaris, including foliar nitrogen levels comparable to those achieved with synthetic fertilizers (urea), as well as good levels of calcium, zinc, and boron.
Keywords: nitrogen; phosphorus; siderophores; abiotic stress; tropical soils